The Treatment of Bipolar Disorder - Li , Xinyue (Transactions on Materials, Biotechnology and Life Sciences, 2024)
As a relatively large class of neurological diseases, bipolar has always been an important object of research and exploration by scientists. When bidirectional patients develop the disease, they are aggressive and a great burden for their families. Therefore, how to treat bipolar has been a hot topic. Current treatments for bipolar include medication, psychotherapy, and physiotherapy. Drug therapy includes mood stabilizers, antidepressants, anticonvulsants, antipsychotics and so on. Psychotherapy is aimed not only at the patient, but also with his or her spouse and relatives. Treatment modalities include psychoanalytic therapy, analytic psychotherapy, cognitive behavioral therapy, suggestive therapy, and supportive therapy. However, different treatment modalities have certain limitations. For example, drugs have certain side effects and may cause complications during treatment. Psychotherapy is more limited by the patient. Physical therapy may cause memory impairment, nausea, headaches, etc. This review is about current treatment modalities for bipolar and their limitations.